2012
DOI: 10.1002/chem.201202248
|View full text |Cite
|
Sign up to set email alerts
|

Linker‐Free, Silica‐Bound Olefin‐Metathesis Catalysts: Applications in Heterogeneous Catalysis

Abstract: A set of heterogenized olefin-metathesis catalysts, which consisted of Ru complexes with the H(2)ITap ligand (1,3-bis(2',6'-dimethyl-4'dimethyl aminophenyl)-4,5-dihydroimidazol-2-ylidene) that had been adsorbed onto a silica support, has been prepared. These complexes showed strong binding to the solid support without the need for tethering groups on the complex or functionalized silica. The catalysts were tested in the ring-opening-ring-closing-metathesis (RO-RCM) of cyclooctene (COE) and the self-metathesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 93 publications
(43 reference statements)
0
41
0
Order By: Relevance
“…In order to increase the scope of the study, Ru‐1 was supported on silica gel before RCM reaction. In a recent study that was reported by Limbach and co‐workers a set of ruthenium catalysts were adsorbed on silica gel and used as heterogeneous catalysts in several olefin metathesis reactions . We tried to adapt the same strategy to our catalyst system.…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase the scope of the study, Ru‐1 was supported on silica gel before RCM reaction. In a recent study that was reported by Limbach and co‐workers a set of ruthenium catalysts were adsorbed on silica gel and used as heterogeneous catalysts in several olefin metathesis reactions . We tried to adapt the same strategy to our catalyst system.…”
Section: Resultsmentioning
confidence: 99%
“…The stability and the strength of catalyst‐support interaction can be optimized by introducing a more compatible ligand in the organometallic complex, as has been demonstrated by Cabrera et al who tested H 2 ITap‐modified Hoveyda‐Grubbs type catalyst . The H 2 ITap, 1,3‐bis(2′,6′‐dimethyl‐4′dimethyl aminophenyl)‐4,5‐dihydroimidazol‐2‐ylidene, ligand acted as a resilient tethering group by getting protonated from the silanol groups of the support material and thus coordinating with the unmodified commercial silica material, most probably as a result of ionic interactions.…”
Section: Metal‐alkylidene Based Heterogeneous Catalyst Systemsmentioning
confidence: 99%
“…Hoveyda‐Grubbs type complexes: (a) SIMes‐modified Hoveyda‐Grubbs II complex; (b) H 2 ITap‐modified Hoveyda‐Grubbs II complex (reproduced with permission) …”
Section: Metal‐alkylidene Based Heterogeneous Catalyst Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…[16][17][18][19][20][21][22][23] Other methodologies such as ring-expansion metathesis polymerization of cycloolefins with cyclic Ru catalysts have also been explored. [24][25][26][27] The particular synthesis of macrocycles from 1,4-PB is only scarcely described, mainly in the context of PB degradation.…”
Section: Introductionmentioning
confidence: 99%